SEASONAL VARIATION IN METEOROLOGICAL PARAMETERS AND BLOOD PRESSURE IN CROATIAN ADULT POPULATION. (June 2022) - Jelakovic, Ana; Srnec, Lidija; Orlic, Mirko; Premuzic, Vedran; Domislovic, Marija; Begic, Zvonimir; Barisic, Karla; Radunovic, Danilo; Prelevic, Vladimir; Dika, Zivka; Stevanovic, Ranko; Jelakovic, Bojan
Abstract : Objective: There are many reports on the seasonality of cardiovascular risk factors particularly of blood pressure (BP). Our aim was to analyze association of BP with various meteorological parameters in random sample of general Croatian adult population. Design and method: EHUH -2 study is nation-wide survey (Croatian Science Foundation) on prevalence, treatment and control of hypertension in Croatia. In 2018–2021 a random sample of 1321 subjects were enrolled. Office blood pressure (BP) and heart rate were measured in sitting position using Omron 3 device three times and average BP values were calculated. Estimated pulse wave velocity (ePWV) was calculated using validated equation. Meteorological data (mean daily 2 m air temperature – T2m, atmosphere pressure, air humidity measured at meteorological stations according to WMO standards) were collected in Croatian Meteorological and Hydrological Service. Results: We found significant difference in systolic and diastolic BP, heart rate and ePWV accorss nalys (Figure 1a and Figure 2), as well significant correlation between all parameters and T2m. (Figure 3 for systolic BP). There is nonsignificant trend in association between systolic BP and air humidity. We failed to find association of diastolic BP, heart rate and ePWV with any of nalysed meteorological parameters. Furthermore, we found inverse association between systolic BP, diastolic BP and heart rate with T2m i.e. we confirmed seasonal fluctuations (Figure 1b). Conclusions: Our data confirmed findings of seasonal (inverse) variation between BP and T2m. Interestingly, we found association of seasonal variation and ePWV. T2m has impact on long-term BP variability but also on ePWV and should be taken into account in clinical research as well as in regular clinical work.